2020
DOI: 10.1371/journal.pone.0227705
|View full text |Cite
|
Sign up to set email alerts
|

Regional adaptations and parallel mutations in Feline panleukopenia virus strains from China revealed by nearly-full length genome analysis

Abstract: Protoparvoviruses, widespread among cats and wild animals, are responsible for leukopenia. Feline panleukopenia virus (FPLV) in domestic cats is genetically diverse and some strains may differ from those used for vaccination. The presence of FPLV in two domestic cats from Hebei Province in China was identified by polymerase chain reaction. Samples from these animals were used to isolate FPLV strains in CRFK cells for genome sequencing. Phylogenetic analysis was performed to compare our isolates with available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The FPV sequences of lineages isolated from distinct hosts intermingle in phylogenetic trees, indicating that this virus easily spreads among distinct species. In the same way, the canine parvovirus (CPV) infects domestic dogs ( Canis lupus familiaris) , wolves ( Canis lupus) and coyotes ( Canis latrans ) [ 75 , 76 ]. Conversely, our phylogenetic analysis showed that evolutionary clades in CHPV are mostly structured according to the host in which this virus was identified.…”
Section: Discussionmentioning
confidence: 99%
“…The FPV sequences of lineages isolated from distinct hosts intermingle in phylogenetic trees, indicating that this virus easily spreads among distinct species. In the same way, the canine parvovirus (CPV) infects domestic dogs ( Canis lupus familiaris) , wolves ( Canis lupus) and coyotes ( Canis latrans ) [ 75 , 76 ]. Conversely, our phylogenetic analysis showed that evolutionary clades in CHPV are mostly structured according to the host in which this virus was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Parvoviruses can cross species barriers to infect less susceptible hosts using single or a few mutations [20]. Several amino acid residue changes in the threefold spike of VP2 could infuence antigenicity and host range [21,22]. Moreover, position 300 and adjacent residues at 299 and 301 in VP2 were separately involved in adapting CPV-2 binding to the canine transferrin receptor; a change in CPV-2VP2 residue 299 (Gly ⟶ Glu) caused the virus to lose its binding ability to canine TfR and 299-Glu severely restricts infection of CPV-2 in dog cells [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…These mutations can differentiate this virus from previously described CPPV-1 variants. Previous analysis of the ancestral reconstruction found that FPV can infect distinct carnivores with few changes in the VP2 gene [ 49 ]. Thus, the FPV-like parvovirus was tentatively named as a potentially novel virus detected in the fishing cats and this may support the first identification of this virus in this species.…”
Section: Discussionmentioning
confidence: 99%